Validation of a New 2D Failure Mechanism for the Stability Analysis of a Pressurized Tunnel Face in a Spatially Varying Sand - Mollon, Guilhem; Phoon, Kok Kwang; Dias, Daniel; Soubra, Abdul-Hamid (Journal of engineering mechanics, 2011)
A new two-dimensional (2D) limit analysis failure mechanism is presented for the determination of the critical collapse pressure of a pressurized tunnel face in the case of a soil exhibiting spatial variability in its shear strength parameters. The proposed failure mechanism is a rotational rigid block mechanism. It is constructed in such a manner to respect the normality condition of the limit analysis theory at every point of the velocity discontinuity surfaces taking into account the spatial variation of the soil angle of internal friction. Thus, the slip surfaces of the failure mechanism are not described by standard curves such as log-spirals. Indeed, they are determined point by point using a spatial discretization technique. Though the proposed mechanism is able to deal with frictional and cohesive soils, the present paper only focuses on sands. The mathematical formulation used for the generation of the failure mechanism is first detailed. The proposed kinematical approach is then presented and validated by comparison with numerical simulations. The present failure mechanism was shown to give results (in terms of critical collapse pressure and shape of the collapse mechanism) that compare reasonably well with the numerical simulations at a significantly cheaper computational cost.